Spontaneous pharyngeal Chlamydia trachomatis RNA clearance. A cross-sectional study followed by a cohort study of untreated STI clinic patients in Amsterdam, The Netherlands. (18th September 2014) - van Rooijen, Martijn S; van der Loeff, Maarten F Schim; Morré, Servaas A; van Dam, Alje P; Speksnijder, Arjen G C L; de Vries, Henry J C
Abstract : Objectives: Pharyngeal Chlamydia trachomatis (chlamydia) might contribute to ongoing chlamydia transmission, yet data on spontaneous clearance duration are rare. We examined the prevalence, spontaneous clearance, chlamydial DNA concentration and genotypes of pharyngeal chlamydia among clinic patients with sexually transmitted infection (STI). Methods: Female patients at high risk for an STI who reported active oral sex and male patients who have sex with men (MSM) were screened for pharyngeal chlamydia RNA using a nucleic acid amplification test. A repeat swab was obtained to evaluate spontaneous clearance in untreated patients with pharyngeal chlamydia. Quantitative chlamydia DNA load was determined by calculating the chlamydia/human cell ratio. Results: Pharyngeal chlamydia was detected in 148/13 111 (1.1%) MSM and in 160/6915 (2.3%) women. 53% of MSM and 32% of women with pharyngeal chlamydia did not have a concurrent anogenital chlamydia infection. In 16/43 (37%) MSM and in 20/55 (36%) women, the repeat pharyngeal swab was negative (median follow-up 10 days, range 4–58 days). Patients with an initial chlamydial DNA concentration above the median were less likely to clear. Of 23 MSM with pharyngeal chlamydia who had sex with a lymphogranuloma venereum (LGV)-positive partner recently or in the past, two were LGV biovar positive (8.7%). Conclusions: The pharynx is a reservoir for chlamydia and LGV, and may play a role in ongoing transmission. Although delay in ribosomal RNA decline after resolution of the infection might have led to an underestimation of spontaneous clearance, in high-risk STI clinic patients, testing the pharynx for chlamydia should be considered.